2019
DOI: 10.15585/mmwr.rr6802a1
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Vaccine: Recommendations of the Advisory Committee on Immunization Practices

Abstract: Summary This report updates the 2010 recommendations from the CDC Advisory Committee on Immunization Practices (ACIP) regarding prevention of Japanese encephalitis (JE) among U.S. travelers and laboratory workers (Fischer M, Lindsey N, Staples JE, Hills S. Japanese encephalitis vaccines: recommendations of the Advisory Committee on Immunization Practices (ACIP). MMWR Recomm Rep 2010;59[No. RR-1]). The report summarizes the epidemiology of JE, describes the JE vaccine that is licensed and available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 186 publications
(235 reference statements)
0
60
0
4
Order By: Relevance
“…Due to the similarity of JEV and WNV, consideration of the animal models used for JEV vaccine testing can provide insight for WNV vaccine development. Mice are the most broadly used model to determine protective efficacy of JEV vaccines, as they generate neutralizing antibody responses upon vaccination and most mouse strains are highly susceptible to WT JEV, so peripheral challenge can adequately assess protection [36,52]. Many studies have demonstrated that JEV inactivated and live, attenuated vaccines in mice induce neutralizing antibody titers that correlate with survival from WT virus challenge [53,54,55,56,57], and the antibodies can provide protection against multiple JEV genotypes [56,57].…”
Section: Animal Models and Evaluation Of Protective Immunitymentioning
confidence: 99%
“…Due to the similarity of JEV and WNV, consideration of the animal models used for JEV vaccine testing can provide insight for WNV vaccine development. Mice are the most broadly used model to determine protective efficacy of JEV vaccines, as they generate neutralizing antibody responses upon vaccination and most mouse strains are highly susceptible to WT JEV, so peripheral challenge can adequately assess protection [36,52]. Many studies have demonstrated that JEV inactivated and live, attenuated vaccines in mice induce neutralizing antibody titers that correlate with survival from WT virus challenge [53,54,55,56,57], and the antibodies can provide protection against multiple JEV genotypes [56,57].…”
Section: Animal Models and Evaluation Of Protective Immunitymentioning
confidence: 99%
“…In areas with endemic JE, the virus primarily affects children, with the vast majority of cases being children aged < 15 years [3][4][5][6][7][8][9][10][11][12]. As there is no effective antiviral treatment, vaccination is the only approach for preventing this virus [13]. In areas with childhood JE vaccination, although the overall incidence of JE has decreased, a greater proportion of adults affected by JE has been reported, predominantly in temperate Asian countries (e.g., Japan, China, South Korea) [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…IXIARO ® -an inactivated VERO cell cultured JEV vaccine -is now immunogenic and safe in children >2 months old and should be considered in those, including women of childbearing age, travelling to endemic areas. 80,81 Togaviruses: Chikungunya Chikungunya virus (CHIKV) is a non-flavivirid mosquito-borne infection that causes significant morbidity and, on occasion, mortality. CHIKV is a Togavirus first described in the 1950s that has spread from Africa to the Indian Ocean and Asia.…”
Section: Zika Virusmentioning
confidence: 99%
“…IXIARO® – an inactivated VERO cell cultured JEV vaccine – is now immunogenic and safe in children >2 months old and should be considered in those, including women of childbearing age, travelling to endemic areas. 80 , 81 …”
Section: Mosquito-borne Infections In Pregnancymentioning
confidence: 99%